The biology and demographic parameters of Aedes albopictus in northern peninsular Malaysia - Nur Aida, Hashim; Hamady, Dieng; Tomomitsu, Satho; AT, Nurita; Che Salmah, Md Rawi; Fumio, Miake; Norasmah, B; Abu Hassan, Ahmad (Elsevier, 2011)
Objective